Choosing Wisely: Envisioning Perinatal Hospice Notification Laws that Inform and Empower - Ashley Flakus (Washington University Law Review, 2020)
Perinatal hospice refers to a cluster of medical services that some individuals choose after the diagnosis of a life-limiting fetal condition. At its core, perinatal hospice involves many kinds of support—including physical, emotional, social, and spiritual—for the pregnant person, family members, and the fetus or newborn from the time of diagnosis to bereavement. The American College of Obstetricians and Gynecologists and the American Academy of Nursing advocate for such programs, which are expanding throughout the United States and the world. Several states have passed perinatal hospice notification laws, which differ in scope but generally require certain pregnant individuals to receive a notification about the availability of perinatal hospice services within the state. Such laws address emotionally difficult matters, and unsurprisingly, they are met with a wide range of reactions. Some find these laws to be an intrusion into a sensitive domestic and medical situation, another manifestation of the same anti-abortion sentiment that has chipped away at bodily autonomy for decades. Others believe laws like these provide essential information to pregnant individuals who may not otherwise learn about a meaningful service to help them through a painful time. This Note will proceed in four parts. Part I will outline the historical development of perinatal hospice as a medical practice and of perinatal hospice notification laws as a legal phenomenon. Part II will identify and compare states’ approaches in crafting (or not crafting) these laws, taking special note of who receives a notification and when. Part III will consider the role of the government, the nature of informed consent, and possible legislative justifications under the police power in passing a perinatal hospice notification law, weighing the legitimacy of different interests and their logical connection (or not) to the laws passed. Finally, Part IV will conclude that two appropriate approaches exist to facilitate meaningfully informed choice in the perinatal hospice context: notifying all eligible individuals of the care they qualify for at the time of diagnosis or deliberately passing no law on the matter at all.
Keywords: Perinatal hospice; Reproductive justice; Informed consent; Health law